PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN LITERASI SAINS SISWA KELAS V SDN 064037 MEDAN TEMBUNG PADA MATERI PERUBAHAN WUJUD BENDA - Tutur Sagala; Nurhairani; Irsan; Nurmayani; Fahrur Rozi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the effect of the Problem Based Learning (PBL) learning model on the scientific literacy skills of fifth-grade students of SDN 064037 Medan Tembung on the material of changes in the state of matter. The research method used is a quasi-experimental with a Nonequivalent Control Group Design. The research sample consisted of 50 students consisting of 28 students in the experimental class and 22 students in the control class. Data collection on scientific literacy skills was carried out through a test instrument that focused on indicators explaining phenomena scientifically. Data analysis techniques used the Shapiro-Wilk normality test, Levene's Test homogeneity test, and hypothesis testing using the Independent Sample t-Test with the help of the SPSS version 27 program. The results of the data analysis showed a significant effect of the application of the Problem Based Learning model on students' scientific literacy skills. This was evidenced by the results of the posttest data t-test which obtained a significance value of 0.03 for the experimental class with an average of 79.10, higher than the control class with a significance value of 0.04 and an average of 71.81. Based on the results of the study, it can be concluded that the PBL learning model has a significant effect on improving the scientific literacy skills of fifth grade students at SDN 064037 Medan Tembung.